Changes in sugar-sweetened beverage purchases across the price distribution after the implementation of a tax in Mexico: a before-and-after analysis - J. C. Salgado Hernández; S. W. Ng; M. A. Colchero (BMC, 2023)
Abstract Background A tax of one-Mexican peso per liter of sugar-sweetened beverage (SSB) came into effect in January 2014 in Mexico as a national health policy to tackle the high overweight and obesity prevalence. Previous studies have shown an overall reduction in SSB purchases after the tax implementation. However, it remains unknown whether and to what extent SSB consumers switched to cheaper taxed beverages, attenuating the potential effect of the policy. Our study's objective was to estimate changes in household purchases of taxed SSBs by tertiles of SSB prices (low, middle, and high) in urban areas after the SSB tax implementation in 2014. Methods Based on purchase data for 2012-2015 from households living in 54 Mexican cities with a population > 50,000 inhabitants, we calculated unit-value SSB prices for the full period and sorted them on a monthly basis to create monthly price tertiles. We merged these price tertiles to household purchases and created average monthly ml/capita/day SSB purchases by price tertile at the city level. We assessed SSB purchase switching patterns before and after the tax implementation through price-tertile stratified linear models. The main variable in the models was a dummy indicator that allowed us to identify the pre-tax period (2012-13) and post-tax period (2014-15). We controlled our models for time trends and contextual economic variables. Results In the regression adjusted models, we found a statistically significant purchase reduction ranging between 10.80 and 13.79 ml/capita/day (p-value < 0.001) across taxed beverages from the middle-price SSB after the tax implementation. We observed no statistically significant reductions in purchases of low-price SSBs and high-price SSBs. Conclusions Our findings show purchase reductions in the middle-price SSBs, which represents ≈30% of the overall SSB purchases in urban Mexico. Future studies should be conducted to test if the redesign of the current the tax, by either doubling the tax amount or taxing sugar content, might reduce more effectively purchases across all SSBs.